PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF STEM BARK OF BAOBAB TREE (Adansonia digitata) ON SOME PATHOGENIC BACTERIA - MT, Adamu; Usman, Musa; Garba, Lawal; A.A, Yarma; A.J, Hadiza; A, Mu‟inat; H.U, Puma; U.A, Tawfiq; A, Salawudeen (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Powdered stem bark of Adansonia digitata was extracted with chloroform and methanol using percolation method of extraction. The chloroform and methanolic extracts were screened for the presence of secondary metabolite using a standard technique. The result of the phytochemical screening indicated the presence of alkaloid, Flavanoid, tannin, reducing sugar and steroid in one or both the extracts. The extracts were further tested on confirmed clinical isolates of Escherichia coli, staphylococcus aureus and proteus mirabilis using disc diffusion method and micro-broth dilution technique. Stem bark extracts of adansonia digitata was found to have antimicrobial activity against the clinical isolates used in the study.